D-Serine Contributes to Seizure Development via ERK Signaling - Ma, Tie; Wu, Yin; Chen, Beibei; Zhang, Wenjuan; Jin, Lang; Shen, Chenxi; Wang, Yazhou; Liu, Yonghong (Frontiers in Neuroscience, 2019)
Seizure is one of the leading neurological disorders. NMDA receptor-mediated neuronal excitation has been thought to be essential for epileptogenesis. As an endogenous co-agonist of the NMDA receptor, D-serine has been suggested to play a role in epileptogenesis. However, the underlying mechanisms still remain unclear. In the current study, we investigated the effects of antagonizing two key enzymes in D-serine metabolism on the development of seizures and the downstream signaling. Our results showed that serine racemase (SR), a key enzyme in regulating the L-to-D-serine conversion, was significantly up-regulated in hippocampal astrocytes in rats and patients who experienced seizure, in comparison with control rats and patients. L-aspartic acid β-hydroxamate (LaaβH), an inhibitor of SR, significantly prolonged the latencies of seizures, shortened the durations of seizures, and decreased the total EEG power in rats. In contrast, D-amino acid oxidase inhibitor 5-chlorobenzo[d]isoxazol-3-ol (CBIO), which can increase D-serine levels, showed the opposite effects. Furthermore, our data showed that LaaβH and CBIO significantly affected the phosphorylation of Extracellular Signal-regulated Kinase (ERK). Antagonizing or activating ERK could significantly block the effects of LaaβH/CBIO on the occurrence of seizures. In summary, our study revealed that D-serine is involved in the development of epileptic seizures partially through ERK signaling, indicating that the metabolism of D-serine may be targeted for the treatment of epilepsy.